KONSEP KEKUDUSAN MENURUT IMAMAT 18 DAN IMPLIKASINYA TERHADAP KONSELING PRANIKAH KAUM MUDA DI GEREJA BETHEL INDONESIA TABGHA BATAM CENTER - Tahan Sitanggang; Ratna Juwita Hutauruk (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2024)
Pre-marital counseling is an activity held for unmarried parties, in connection with their wedding plans. These parties come to the counselor to make their decisions so that they are more stable and can make better adjustments in the future. Marriage counseling or what is commonly called marriage counseling is an effort to help the prospective bride and groom. Marriage counseling is carried out by professional counselors. The goal is that they can develop and be able to solve the problems they face through ways of mutual respect, tolerance, and communication, in order to achieve family motivation, development, independence, and the welfare of all family members. The purpose of personal counseling specifically has the main and foremost goal in mentoring, namely introducing the counselee to Jesus Christ with the power of the Holy Spirit and the grace of God and helping the counselee to become like Christ. This counseling is a service process so that the counselee has a life change and experiences recovery from the intervention of the Holy Spirit and accepts the Lord Jesus as a personal Savior so that the counselee lives and grows in a better spirituality. This service can be done by a counselor or a servant of God to help church members free from dark powers. Through this counseling service, the counselor will check the personal acceptance of Jesus; confession to God; ask forgiveness from God; deliverance prayer service; convinced of a new identity in Christ. Discipleship ministry (follow up) is very important for people who have just been released from the bonds of dark power. The strategy that the church must do is to make disciples or guide personally so that the counselee knows more about Jesus and grows more in Jesus Christ. Holiness is a state or quality of being holy. Holiness is a sign of a believer's spiritual life that must be continuously strived for, including ethical behavior. The Christian life and holiness are an inseparable unity in the believer. God's holiness has a lot to do with the people He chooses. Election/covenant is a unique expression of God's holiness. Because God is holy, God also requires His people to live holy lives (Leviticus 11:44). God shows His holiness in His actions for the salvation of the people He has chosen (Num. 20:13).